The given equation has been solved in the table.

\begin{tabular}{|c|c|}

\hline

Step & Statement \\

\hline

1 & [tex]$3x - 10 = -16$[/tex] \\

\hline

2 & [tex]$3x - 10 + 10 = -16 + 10$[/tex] \\

\hline

3 & [tex]$3x = -6$[/tex] \\

\hline

4 & [tex]$\frac{3x}{3} = \frac{-6}{3}$[/tex] \\

\hline

5 & [tex]$x = -2$[/tex] \\

\hline

\end{tabular}

Use the table to complete each statement.

In step 2, the [tex]$\square$[/tex] property of equality was applied.

In step 4, the [tex]$\square$[/tex] property of equality was applied.

1. The initial equation provided is [tex]\(3x - 10 = -16\)[/tex].

2. In step 2, the equation is [tex]\(3x - 10 + 10 = -16 + 10\)[/tex]. To simplify the equation, we added 10 to both sides. This preserves equality because whatever you do to one side of the equation, you must do to the other side. This application is known as the

3. Simplifying step 2, we get [tex]\(3x = -6\)[/tex].

4. In step 4, [tex]\(\frac{3x}{3} = \frac{-6}{3}\)[/tex]. To isolate [tex]\(x\)[/tex], we divided both sides by 3. This application is known as the

5. Simplifying step 4, we get [tex]\(x = -2\)[/tex].

Using this detailed walkthrough, we can determine the correct properties of equality applied in each step.

So,

1. In step 2, the

2. In step 4, the